FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN INFEKSI TINEA PEDIS PADA PETANI KARET DI KELURAHAN LIPATKAIN KABUPATEN KAMPAR TAHUN 2024 - Putri Retno; Nurmaliza Hasan; Nursofi Ali; Yuharika Ratih (LPPM Universitas Abdurrab, 2025)
Tinea pedis is a dermatophytosis of the feet, especially between the toes and soles of the feet. The cause of this disease is Tricophyton rubrum with signs of fissures surrounded by fine and thin scales. Tinea pedis is the second highest occupational disease in Europe. In Indonesia, tinea pedis is one of the top ten skin diseases and 65% of this disease is related to work, especially rubber farmers. This study was conducted to determine the relationship between the habit of washing feet after work and the incidence of tinea pedis infection in rubber farmers in Lipat Kain Village, Kampar Kiri District, Kampar Regency. This study used an observational analytical method with a cross-sectional approach. The sampling technique was total sampling that had met the inclusion criteria. Data were analyzed using the chi square test. The results of 40 samples obtained as many as 23 respondents with the habit of not washing their feet after work, around 16 (69.6%) respondents were infected with tinea pedis and as many as 17 respondents with the habit of washing their feet after work had no incidence of tinea pedis infection. Based on the chi square test with P = 0.000, the p value <0.05 was obtained, indicating that there is a significant relationship between the habit of washing feet after work and the incidence of tinea pedis infection in rubber farmers. Clean and healthy living behavior by maintaining cleanliness of the feet through the habit of washing feet after work for rubber farmers can reduce the incidence of tinea pedis infection